Nicotine induces endothelial dysfunction and promotes atherosclerosis via GTPCH1 - Li, Jingyuan (J Cell Mol Med, 2018)
Smoking is a major preventable risk factor for atherosclerosis. However, the causative link between cigarette smoke and atherosclerosis remains to be established. The objective of this study is to characterize the role of GTP cyclohydrolase 1 (GTPCH1), the rate‐limiting enzyme for de novo tetrahydrobiopterin (BH4) synthesis, in the smoking‐accelerated atherosclerosis and the mechanism involved. In vitro, human umbilical vein endothelial cells were treated with nicotine, a major component of cigarette smoke, which reduced the mRNA and protein levels of GTPCH1 and led to endothelial dysfunction. GTPCH1 overexpression or sepiapterin could attenuate nicotine‐reduced nitric oxide and ‐increased reactive oxygen species levels. Mechanistically, human antigen R (HuR) bound with the adenylateuridylate‐rich elements of the GTPCH1 3′ untranslated region and increased its stability; nicotine inhibited HuR translocation from the nucleus to cytosol, which downregulated GTPCH1. In vivo, nicotine induced endothelial dysfunction and promoted atherosclerosis in ApoE(−/−) mice, which were attenuated by GTPCH1 overexpression or BH4 supplement. Our findings may provide a novel and promising approach to atherosclerosis treatment.